+0  
 
+1
195
1
avatar+549 

thank you in advance

 

winkwinkwink

 Apr 21, 2018
 #1
avatar+95227 
+1

Hi Linx7    laugh

 

\(\frac{3x-2}{4}-\frac{2x-5}{3}=\frac{1+x}{6}\\ \text{lowest common denominator is 12}\\ 12\times \left(\frac{3x-2}{4}-\frac{2x-5}{3}\right)=12 \times \left(\frac{1+x}{6}\right)\\ 3(3x-2)-4(2x-5)=2(1+x)\\ 9x-6-8x+20=2+2x\\ x+14=2x+2\\ 12=x\\ x=12\)

.
 Apr 21, 2018

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.